Politik Hukum Pertanian Indonesia Dalam Menghadapi Tantangan Global - Tity Wahju Setiawati; Mardjo Mardjo; Tutut Ferdiana Mahita Paksi (Jurnal Hukum IUS QUIA IUSTUM, 2019)
The structure of agricultural policy in Indonesia is still reaping with many problems which include the conversion of agricultural land to non-agricultural land, the low level of the farmers’ welfare, as well as the land reform policy. To unravel the causes of these problems, this research intends to first, discuss the politics of agricultural law in Indonesia from the Old Order era to the Reformation, and second, to offer ideas for improving the development of agricultural law politics in order to face the global challenges. This study uses a normative legal research method by reviewing the statutory approach and historical approach. The research concluded that, first, during the Old Order the political direction of the agricultural sector was emphasized on the i1nventory of agricultural and plantation land. During the New Order era, the political direction of the agricultural sector was divided into two, namely, the direction of food sovereignty and semi-industrial agriculture. During the reform period, the dominance of the influence of foreign capitalism in the legislation. Second, the ideas offered to face the global challenges are by building a legal policy for agriculture based on economic democracy as initiated by Bung Hatta.